Dihydro-2H-thiopyran-3(4H)-one-1, 1-dioxide – a versatile building block for the synthesis of new thiopyran-based heterocyclic systems. (4th January 2018) - Palchykov, Vitalii A.; Chabanenko, Roman M.; Konshin, Valeriy V.; Dotsenko, Victor V.; Krivokolysko, Sergey G.; Chigorina, Elena A.; Horak, Yuriy I.; Lytvyn, Roman Z.; Vakhula, Andriy A.; Obushak, Mykola D.; Mazepa, Alexander V.
Abstract : Three series of new cyclic sulfones have been prepared by a one-pot multi-component reactions. Abstract : Three series of new cyclic sulfones have been prepared by a one-pot multi-component reaction (MCR) starting from the readily available dihydro-2 H -thiopyran-3(4 H )-one-1, 1-dioxide. The in silico screening of the synthesized compounds revealed their high anti-inflammatory, antiarthritic, antiasthmatic and antiallergic potential coupled with the strong probability levels of cystinyl aminopeptidase inhibition. The key structures were confirmed by 2D NMR techniques.